Half-hearted Administrative Reform: a Study of Surabaya City Development - Wahyuni*, Sri; Umiyati, Sri (Universitas Syiah Kuala, 2023)
This research aims to evaluate the extent to which administrative reforms have been implemented and the extent to which their impact is visible in the city's development. The method used is a literature review. It is hoped that the results of this research will contribute to understanding the dynamics of administrative reform at the local level and their impact on the urban development process. This article can be an important reference for practitioners, policymakers, and researchers who are interested in understanding the role of public administration in urban development in Indonesia, especially in the context of Surabaya.